Application of morphometric study to discriminate Pteridium aquilinum (L.) Kuhn subsp. pinetorum (C. N. Page & R. R. Mill 1995) J. A. Thomson in Poland - Zenkteler, Elżbieta; Nowak, Oskar (Biodiversity: Research and Conservation, 2019)
Pteridium aquilinum subsp. pinetorum is one of two morphologically distinct taxa of the genus Pteridium identified in Poland. In order to confirm their distinctively recognizable morphology, nine features defining each of these taxa were subjected to a morphometric analysis. These features, including taxonomic characters of vegetative structures, were measured or counted for their most comprehensive descriptions. The measurements were also expressed as ratios of two characters (length of the first and second pairs of leaflets) to prevent the size of fronds from influencing the results. Unique features of bracken, such as: frond and pinnae shape and orientation; basal pinna structure; ultimate segment of pinnae and pinnula shape and size; frond expansion sequencing; frond lamina texture, shape and pubescence were treated descriptively. Canonical discriminant analysis was employed for a morphometric study of quantitative characters. On their basis, two taxa – P. aquilinum subsp. aquilinum and P. a. subsp. pinetorum were determined.